2014
DOI: 10.5539/ass.v10n4p131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Organizational Justice and Job Satisfaction as Perceived by Jordanian Physical Education Teachers

Abstract: This study aimed at exploring the relationship between organizational justice and job satisfaction as perceived by Jordanian physical education teachers. Participants consisted of 166 physical education teachers selected from public schools in Jordan. Organizational Justice Scale and Job in General Scale were used to collect the data. The findings revealed that the majority of physical education teachers were satisfied with their job in general and their perceptions about organizational justice were positive. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
2
10
0
6
Order By: Relevance
“…Therefore, it can be suggested that the process of the distribution of rewards and the decisionmaking process should be expanded to make it possible for employees to take part in them and to improve the perceptions of these processes. The findings by Altahayneh et al (2014), Annamalai et al (2010), Basım et al (2009), Hoy and Tarter (2004, Niehoff and Moorman (1993), Polat and Kazak (2014) and Yeşil and Dereli (2012) suggest that when the employees' perceptions about organizational justice is higher, many variables such as organizational citizenship, job satisfaction, organizational loyalty, performance and organizational trust are positively affected. Thus, organizational justice is a very significant contributor of the organizational citizenship behavior of the employees.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, it can be suggested that the process of the distribution of rewards and the decisionmaking process should be expanded to make it possible for employees to take part in them and to improve the perceptions of these processes. The findings by Altahayneh et al (2014), Annamalai et al (2010), Basım et al (2009), Hoy and Tarter (2004, Niehoff and Moorman (1993), Polat and Kazak (2014) and Yeşil and Dereli (2012) suggest that when the employees' perceptions about organizational justice is higher, many variables such as organizational citizenship, job satisfaction, organizational loyalty, performance and organizational trust are positively affected. Thus, organizational justice is a very significant contributor of the organizational citizenship behavior of the employees.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from those, other studies have focused on different aspects of organizational justice and the relationships among them. For example, offensive acts (e.g., Özdevecioğlu, 2003), job satisfaction (e.g., Altahayneh, Khasawneh & Abedalhafiz, 2014;Yelboğa, 2012;Yeşil & Dereli, 2012;Yıldırım, 2007), organizational trust and performance (e.g., Annamalai, Abdullah & Alazidiyeen, 2010), nepotistic behaviors (e.g., Polat & Kazak, 2014), gender (e.g., Simpson & Kaminski, 2007), and entrepreneurship (e.g., Basım, Meydan & Şeşen, 2009), all these suggesting that the perception of justice of the individuals affects many variables such as job satisfaction, performance and others.…”
Section: Introductionmentioning
confidence: 99%
“…Menurut penelitian yang dilakukan Altahayneh et al (2014), menunjukkan bahwa keadilan organisasional berpengaruh positif dan signifikan terhadap kepuasan kerja. Penelitian dari Putra dan Putra (2014), menunjukan bahwa keadilan organisasional berpengaruh positif pada kepuasan kerja karyawan.…”
Section: Penelitian Terdahuluunclassified
“…On the other hand, job satisfaction is defined as the feeling an employee has about his/her job and/or reality (Locke, 1976). Numerous researchers have discovered a positive relationship between distributive justice and job satisfaction (Ali & Saifullah, 2014;Altahayneh, Khasawneh & Abedalhafiz, 2014;Fatt, Khin & Heng, 2010;Hao, Hao & Wang, 2016;Heidari & Saeedi, 2012;Rahman, Haque, Elahi & Miah, 2015;Saadati, Saadati, Asghari, Bidgoli, Ghodsi & Bidgoli, 2016). Based on this reason, it is hypothesized as follows: Hypothesis (H) 1: A positive relationship exists between distributive justice and job satisfaction.…”
Section: Relationship Between Distributive Justice and Job Satisfactionmentioning
confidence: 99%